Variations to the Nanotube Surface for Bone Regeneration - Christine J. Frandsen; Karla S. Brammer; Sungho Jin (International Journal of Biomaterials)
The complex mechanisms of the bone cell-surface interactions are yet to be completely understood, and researchers continue to strive to uncover the fully optimized implant material for perfect osseointegration. A particularly fascinating area of research involves the study of nanostructured surfaces, which are believed to enhance osteogenic behavior, possibly due to the mimicry of components of the extracellular matrix of bone. There is a growing body of data that emphasizes the promise of the titanium oxide (TiO2) nanotube architecture as an advanced orthopedic implant material. The review herein highlights findings regarding TiO2 nanotube surfaces for bone regeneration and the osteogenic effects of minute changes to the surface such as tube size and surface chemistry.